System Dynamics Model of Technology Transition under Resource Constraints: A Catfish Farming Case - Endang Prasetyaningsih; Puti Renosori; Selamat Selamat; Dadan Wahyudi (Jurnal Improsci, 2025)
Background. This study deals with a System Dynamics (SD) model to investigate technology transition under resource constraints, using small-scale catfish farming as a case study. In this context, land availability constitutes the resource constraint. To address this constraint, it is necessary to achieve catfish productivity gains through technological intensification, such as the use of aquaponics. Methods. The SD model captures feedback interactions among production, operating costs, revenue, profit, and reinvestment by setting aside a portion of profits. The SD model's behavior is analyzed by generating six scenarios over 25 years to examine the effects of feed price fluctuations, fingerling price fluctuations, and alternative reinvestment rates. Model outcomes were evaluated using production, profitability, and the benefit–cost ratio (BCR) as an economic performance indicator. Result. The results show that feed and fingerling price fluctuation exerts a strong negative effect on profitability and economic feasibility, while higher reinvestment rates accelerate aquaponics adoption and improve long-term performance. Conclusion. BCR analysis indicates that technology transition in land-limited catfish farming is feasible only when BCR remains above unity, supporting sustained reinvestment. Implementation. The study highlights the importance of reinvestment strategies and feed and fingerling costs management in enabling resilient technological upgrading in spatially constrained aquaculture systems.